A COMPARATIVE STUDY OF INDONESIAN AND MALAYSIAN MONETARY POLICY - Wulandari, Neni Sri (Fakultas Pendidikan Ekonomi dan Bisnis, 2019)
Abstract. The important role of monetary policy lies in its ability to influence price stability, economic growth, employment opportunities and balance of payments. Therefore it is very important for the central bank to establish monetary policy in a country especially for two developing countries such as Indonesia and Malaysia. The purpose of this study is to determine the implementation of monetary policy in Indonesia and Malaysia. The method used is the study of literature by comparing the monetary policies of Indonesia and Malaysia. The results of this study indicate that Indonesian monetary policy is strongly influenced by interest rates while monetary policy in Malaysia is influenced by direct loans without ties through open tenders, repo transactions, auction of Bank Negara Monetary Notes (BNMN), auction of Bank Negara Interbank Bills (BNIBs) and foreign exchange (FX). The implications of this study are expected to be able to add new inclusions regarding the implementation of monetary policy in Indonesia and Malaysia.Keyword. monetary policy, comparative study, indonesia, malaysia.